Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1159/000150365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HCV Structural Proteins Expressed in Various Animal Cells

Abstract: Hepatitis C virus (HCV) is a main causative agent for transfusion-associated and sporadic cases of non-A, non-B hepatitis throughout the world. HCV has a positive-strand RNA of about 9,400 nucleotides as its genome, whose organization is similar to those of animal pestiviruses or human fiaviviruses. In spite of the lack of an effective replication system in tissue culture cells, genes coding for viral proteins of HCV have been identified. The putative nucleocapsid (p22) and envelope (gp35 and gp60) proteins ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…2 a), which is compatible with the size of the core protein previously reported (Harada et al, 1991 ;Matsuura et al, 1994 ;Santolini et al, 1994). There was no significant difference in the levels of core protein in the liver between the C21 and C49 lines.…”
Section: Expression Of the Core Proteinsupporting
confidence: 90%
See 1 more Smart Citation
“…2 a), which is compatible with the size of the core protein previously reported (Harada et al, 1991 ;Matsuura et al, 1994 ;Santolini et al, 1994). There was no significant difference in the levels of core protein in the liver between the C21 and C49 lines.…”
Section: Expression Of the Core Proteinsupporting
confidence: 90%
“…One of the major issues regarding the pathogenesis of HCV-associated liver lesion is whether the HCV proteins have direct effects on pathological phenotypes. Although several strategies have been used to characterize the hepatitis C viral proteins (Grakoui et al, 1993 ;Harada et al, 1991 ;Lanford et al, 1993 ;Matsuura et al, 1992Matsuura et al, , 1994Ralston et al, 1993 ;Santolini et al, 1994), the relationship between protein expression and disease phenotype has not been clarified. We previously established transgenic mouse lines in which the HCV envelope proteins are efficiently expressed in the liver (Koike et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…DEN and JEV are both members of the Flaviviridae family, which also includes HCV (35,50). The HCV core protein shares 22 and 30% homology with the DEN and JEV core proteins within the N-terminal 50 amino acids, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Some in vivo studies with transgenic mice have also raised the idea of the role of HCV core expression in the induction of HCC (46). Although HCV core is mostly a cytoplasmic protein located on endoplasmic reticulum membranes and around lipid vesicles, C-terminally truncated core translocates to the nucleus, where it might exert distinct biological effects (47)(48)(49). During natural HCV infection, some reports have suggested that such truncated core might be identified in the tumor tissues of patients with HCC (50,51).…”
Section: Discussionmentioning
confidence: 99%